2005
DOI: 10.1016/j.intcom.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

‘It's just like you talk to a friend’ relational agents for older adults

Abstract: Relational agents-computational artifacts designed to build and maintain long-term socialemotional relationships with users-may provide an effective interface modality for older adults. This is especially true when the agents use simulated face-to-face conversation as the primary communication medium, and for applications in which repeated interactions over long time periods are required, such as in health behavior change. In this article, we discuss the design of a relational agent for older adults that plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
238
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(245 citation statements)
references
References 31 publications
5
238
0
2
Order By: Relevance
“…In addition to the theoretical reasons why ECAs may be ideal interfaces for patients with inadequate health literacy, described earlier, patients interviewed in the pilot studies that preceded the two trials provided a better understanding of their reasons for accepting the technology (Bickmore, Pfeifer, & Jack, 2009;Bickmore, Caruso, Clough-Gorr, & Heeren, 2005). Patients in both pilots indicated that the system was very easy to use, even if they had little or no experience with computers:…”
mentioning
confidence: 99%
“…In addition to the theoretical reasons why ECAs may be ideal interfaces for patients with inadequate health literacy, described earlier, patients interviewed in the pilot studies that preceded the two trials provided a better understanding of their reasons for accepting the technology (Bickmore, Pfeifer, & Jack, 2009;Bickmore, Caruso, Clough-Gorr, & Heeren, 2005). Patients in both pilots indicated that the system was very easy to use, even if they had little or no experience with computers:…”
mentioning
confidence: 99%
“…Emotions affect the explicit message conveyed during the interaction and is frequently mentioned in the literature as the most important factor in establishing a working alliance in AAL applications [20,22]. They change people's voices, facial expressions, gestures, and speech speed; this is a phenomenon addressed as emotional coloring [1].…”
Section: Modeling the User Emotional Statementioning
confidence: 99%
“…Greeting and "farewell" were chosen due to their importance in framing interactions within a larger timeframe [9].…”
Section: B Robot Behavioursmentioning
confidence: 99%
“…The use of non-verbal cues to convey a sense of shared history and relationship in order to build and maintain relationships between an agent and its user has been addressed by Bickmore et al [6][7][8][9] which has proposed the use of such strategies and demonstrated the impact of their 1 use with anthropomorphic virtual conversational agents. Others have also highlighted the appropriate use of nonverbal cues as important for human-robot interactions, for example, [10,11].…”
mentioning
confidence: 99%